The modelling of earthquake magnitude in the southern part of Java Island using geographically weighted regression. (2022) - -, Sediono; Mardianto, M. Fariz Fadillah; Ulyah, Siti Maghfirotul; Pangestu, Alvito Aryo; Susanti, Rita; Firdaus, Haydar Arsy
No abstract available